Redesigning of CRSM Editor - Joshi, Arun (My University, 2007)
Reactive systems are usually very complex. Various programming languages for reactive systems like Esterel, Argos, Statecharts and Lustre have been proposed for reactive ystems. Most of these synchronous languages are useful only for centralized controllers. There are many distributed controller applications which requires more than one local controller controlling their local environment and also communicating with other controllers to maintain the global state of the system. Communicating Reactive state Machines (CRSM) [3]is a pictorial language which provides communication primitives for such kind of distributed application. This project is a part of a broader project for designing an environment for CRSM, which includes development of verification tool, translator, editor and simulator for CRSM. This project is redesigning the existing editor for verification environment of CRSM programs.
Keywords: Programming languages; Software engineering; CRSM; Communicating reactive state machines; Computer science